A casting strategy to produce 3D bulk monolithic carbon and N-doped carbon nanosheets with high surface area and low volume - Yeganeh Ghotbi, M. (Elsevier B.V., 2020)
Due to the importance of the 3D carbon monoliths and their vast applications in electrochemical energy, catalysis and gas reservoir devices, different strategies have been made on the synthesis/fabrication of 3D graphene or graphene-like products. Nevertheless, the existing 3D carbon bodies mostly suffer from low accessible surface area (ASA), poor mechanical properties and above all, high volume values, in spite of the today's need for making small architectures. Moreover, synthesis/fabrication approaches of desirable 3D bodies with particular size and shape remain unavailable, yet. Herein, we report a new simple method based on the idea of layered nanohybrids/nanoreactors for simultaneous synthesis and fabrication of 3D monolithic bodies composed of pure and N-doped carbon nanosheets. X-ray diffraction, Fourier transform infrared, scanning electron microscopy, X-ray photoelectron spectroscopy and surface area and pore analysis results indicated that the robust pure and N-doped carbon bodies have high surface area values in low volumes constructed by carbon layers with turbostratic structure. As the N-doped 3D carbon sample shows a surface area of 27.83 m2 in a 0.221 cm3 volume. Moreover, the 3D monolithic carbon bodies are porous materials with large pore volume up to 2.1 cm3/g which can be used in various practical applications. Â© 2019 Elsevier Inc.